Clinical evaluation and biological understanding of the early step-by-step healing after periodontal microsurgery: A case report with PES analysis comparing initial and 31-day result - Sergio Kahn; Larissa Zarjitsky de Oliveira; Alexandra Tavares Dias; Gustavo Vicentis de Oliveira Fernandes (Journal of Advanced Periodontology and Implant Dentistry)
Microsurgery has evolved, permitting faster vascularization and healing than macro-interventions, reducing tissue trauma and obtaining precise wound closure. Therefore, this study aimed to detail the initial healing steps after the periodontal microsurgical procedure. A -26 year-old female had a localized recession (anterior lower tooth, recession type1-), with the absence of local keratinized tissue width (KTW) and adjacent gingival thickness (GT)<1 mm. After oral prophylaxis and occlusal adjustments, the pink esthetic score was performed (5 points), followed by the microsurgery procedure. Prior to inserting the subepithelial connective tissue graft (SCTG), the epithelial layer was removed, and the root surface was biomodified. Two days postoperatively, it was possible to observe a white layer from the SCTG in the gingival margin, decreasing after 4 days. In 6 days, the sutures were removed; no graft and volume loss was observed. For 9 days, the volume was the maintenance. Nevertheless, there was a reduction in tissue volume in the facial zone. After 11 and 13 days, an improved healing process was found, whereas, after 16 days, it was possible to report stable tissues, which was confirmed after 31 days, with a significant GR reduction and an increase in KTW and GT. Moreover, the final pink esthetic score (PES) was 9. Microsurgery had a faster healing and predictable outcome, suggesting reduced trauma, which may allow a quicker suture removal without jeopardizing the outcomes.